2013
DOI: 10.1152/physiolgenomics.00117.2012
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative characterization of changes in the cardiac mitochondrial proteome during anesthetic preconditioning and ischemia

Abstract: Bienengraeber M, Pellitteri-Hahn M, Hirata N, Baye TM, Bosnjak ZJ, Olivier M. Quantitative characterization of changes in the cardiac mitochondrial proteome during anesthetic preconditioning and ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…The partial inhibition of complex III is already discussed to account for the cardioprotective properties of volatile anesthetics [39]. A recent proteomics study also detected decreased levels of UQCRC1 in isoflurane-preconditioned heart [16]. In accordance to this we found UQCRC1 to be diminished especially in response to the washout phases during the preconditioning protocol.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The partial inhibition of complex III is already discussed to account for the cardioprotective properties of volatile anesthetics [39]. A recent proteomics study also detected decreased levels of UQCRC1 in isoflurane-preconditioned heart [16]. In accordance to this we found UQCRC1 to be diminished especially in response to the washout phases during the preconditioning protocol.…”
Section: Discussionsupporting
confidence: 85%
“…For instance Xiao and co-workers demonstrated several mitochondrial protein expression changes of proteins related to ATP generation and transport in a setup analysing delayed sevoflurane-preconditioning [15]. Bienengraeber et al could show that isoflurane-induced preconditioning predominantly affected complexes of the electron transport chain in the cardiac mitochondrial proteome [16]. In addition, metabolomics studies strengthen the link between bioenergetic profiles and cardioprotection [40,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AGEs upregulated the ROS production, Cyt c release (He et al, 2011;Knels et al, 2008), and then promoted the activation of casapases and led to target cell apoptosis (Yoshimaru et al, 2008). Moreover, anesthetics also exert pressure on mitochondria and even promote mitochondrial dysfunction and lead to apoptotic cell death (Bienengraeber et al, 2013;Zhang et al, 2010). Our results in mitochondrial function analysis confirmed that AGEs and etomidate could synergistically induce oxidative stress.…”
Section: Discussionsupporting
confidence: 63%
“…The same protocol has been established in our previous studies and mirrors a clinically relevant dosage. 17,18 Control cells remained in the same incubator throughout the experiment. Isoflurane-exposed cells were removed from the sealed chamber and placed with control cells for 15 minutes to allow for washout of the volatile anesthetic before RNA isolation.…”
Section: Methodsmentioning
confidence: 99%